A global study into Indian women’s experiences of domestic violence and control: the role of patriarchal beliefs - Satyen, Lata; Bourke-Ibbs, Madeleine; Rowland, Bosco (Frontiers in Psychology, 2024)
Domestic violence (DV) is a serious and preventable human rights issue that disproportionately affects certain groups of people, including Indian women. Feminist theory suggests that DV results from the patriarchal ideologies of male perpetrators; however, this has not been examined in the context of women from the Indian subcontinent. This study examined Indian women's experiences of abuse (physical, sexual, and psychological) and controlling behaviour across 31 countries by examining the relationship between the patriarchal beliefs held by the women's partners and the women's experience of DV. This study uses an intersectional feminist framework to examine the variables. Data from an online questionnaire was collected from 825 Indian women aged between 18 and 77 years (M = 35.64, SD = 8.71) living in 31 countries across Asia (37.1%), Europe (18.3%), Oceania (23.8%), the Americas (16.1%) and Africa (3.2%) and analyzed using a hierarchical linear regression. A majority of participants (72.5%) had experienced at least one form of abuse during their relationship, and over a third (35.1%) had experienced controlling behaviour. In support of the central hypotheses, after controlling for potential confounders, women whose partners showed greater endorsement of patriarchal beliefs were less likely to have access to freedom during their relationship (ß = -0.38, p < .001) and were more likely to have been abused by their partner or a member of his family (ß = 0.34, p < .001). The findings of this study highlight the need to engage with men in Indian communities through culturally-tailored intervention strategies designed to challenge the patriarchal ideologies that propagate, justify, and excuse DV.